PENGARUH UPAYA PEMASARAN MEDIA SOSIAL TERHADAP TANGGAPAN KONSUMEN YANG DIMEDIASI EKUITAS MEREK PADA PENGGUNA PRODUK MINISO DI KOTA BANDA ACEH - Jauza Nabila Syaeful, Sulaiman (Departemen Manajemen, 2018)
This study aims to examine the effect of Social Media Marketing Efforts on Consumer Response mediated by Brand Equity to MINISO consumer in Banda Aceh. Sampling method on this research using Purposive Sampling with samples of 155 respondents. The results of this study indicate that the variables of Social Media Marketing Effort and Brand Equity have a significant effect on Consumer Response. Furthermore, Brand equity variables mediate partially between the Social Media Marketing Efforts on Consumer Response.